The Working-Class Struggle for Welfare in Britain - Matthews, David (Monthly review (New York. 1949), 2018)
The experience of the British working class from the late nineteenth century to the current era of austerity illustrates that for labor, the welfare state is not just a mechanism to enhance the accumulation of capital or reinforce oppression. From the beginning, it was a vital part of the class struggle—and so it remains today.Click here to purchase a PDF version of this article at the Monthly Review website.